ANTESEDEN DAN KONSEKUENSI KETERLIBATAN MEREK KONSUMEN PADA PRODUK PEMBERSIH - Rani Dwi Hapsari; Zunan Setiawan; Purwoko Purwoko; Fitroh Adilla (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study investigates the impact of social media marketing elements, namely entertainment, customization, interaction, electronic word of mouth and trends, on consumer engagement on brands and brand knowledge. This study collected 233 usable responses from respondents who are social media users. Overall, the sample profile is broadly representative of social media users in the Special Region of Yogyakarta and according to the research objectives. Testing the hypothesized relationship, an online survey was used to collect data from a sample consisting of all consumers who had used Magic Clean cleaning products in the Special Region of Yogyakarta. This online survey takes approximately 10 minutes to complete. Invitations to participate in surveys and links to questionnaires have been posted on several social media. The questionnaire featured a 5-point Likert scale, using measurement items adopted from the study of Cheung, Pires, and Rosenberger (2020). This analysis features partial least squares structural equation modeling (PLS–SEM) using SmartPLS v3.2.8. This study also finds that consumer involvement in brands has a strong and significant influence on brand awareness and brand image. These results mean that consumer engagement in brands should not only be considered as a means to enhance brand recall and recognition, but as an important factor in building brand image.